082 Fulminant ADEM mimicking a glial tumour. (23rd August 2021) - Qiu, Jessica; Thompson, Elizabeth; Fulham, Michael J; Krishnaswamy, Mrudula; Buckland, Michael E; Khoo, Liane; Urriola, Nicolás; Parratt, Kaitlyn
Abstract : Introduction: We describe an atypical case of fulminant acute disseminated encephalomyelitis (ADEM). Case: A 47 year-old Southeast Asian lady presented after developing headache, aphasia and right hemiparesis over four hours, preceded by dry cough for one week and fevers for two days. CT brain noted vasogenic oedema without enhancement in the left frontoparietal lobe, midline shift and incidental upper lobe consolidation and calcified hilar lymph nodes on CT chest. A provisional diagnosis of cerebral tuberculosis was made. MRI brain noted gross mass effect and T2 hyperintensity localised to the white matter, crossing the midline and extending directly to the pons without significant restricted diffusion. Ill-defined enhancement was noted without tuberculomas or leptomeningeal enhancement. MRI spine was unremarkable, as were extensive tests for infectious aetiologies on serum, sputum and CSF. A glial tumour was suspected; FDG-PET-CT did not show regions of increased metabolism. As the patient rapidly deteriorated, empirical corticosteroids, plasmapheresis and IVIg were commenced just prior to decompressive craniectomy and biopsy four days post-presentation. The biopsy demonstrated reactive astrocytosis and perivascular macrophages localised to the white matter, as well as perivascular and perivenular demyelination consistent with ADEM. Absence of a significant lymphocytic infiltrate may have been influenced by the short time to biopsy. The patient made a remarkable recovery following cyclophosphamide, achieving independence in mobility and driving within two months. Conclusion: Atypical features of fulminant ADEM highlight the need for a high index of clinical suspicion and early institution of aggressive immunosuppressive therapy for a favourable outcome.